Advocating the Temporary Rights to Work for Refugees and Asylum Seekers in Transit in Indonesia - Sianturi, Marupa Hasudungan; Viartasiwi, Nino (UI Scholars Hub, 2021)
Refugees and asylum seekers are stuck in three to unknown years of protracted transit in Indonesia in their route to reach a destination country. The status of foreign refugees and asylum seekers has deprived them access to basic human needs such as the right to earn a living, education, and healthcare service. This study focuses on the issue of the prohibition to work for refugees and asylum seekers by reviewing the law and regulation concerning refugee protection, rights to work for foreigners, and fundamental human rights. In addition, a review of international norms and conventions on human rights, as well as a focus group discussion with academia on the topic of access to work for refugees, were also conducted. The main questions to be addressed are: first, what is the legal basis for the policy to deprive the rights to work for refugees and asylum seekers in Indonesia? Second, is the regulation used as the legal basis for the policy coherent with other regulations? Third, the study also probes the possible regulations that will allow access to work. Finally, the study departs from the standpoint that while deprivation to work is inherently a human rights violation, the state's right to protect economic wellbeing from presumed threats for its citizens is also rightful. As a contribution to the discourse, this study offers a perspective that can be used as the basis for a legal breakthrough for refugees and asylum seekers access to the economy that balances the need to respect refugees' human rights and accommodate state concerns regarding job security and economy for the citizens.